Association between left atrial strain and left ventricular diastolic dysfunction - Andy Tze Yang, Ko; Oon, Yen Yee; Chung, Bui Khiong; Julian Wei Ee, Tong; Cheah, Cheng Foong; Esteban Yu Hern, Chin; Chiang, Kit How; Leong, Lai Kuan; Khor, How Kiat; Chow, Han Bing; Chan, En Ze; Ling, Hwei Sung; et al. (Elsevier B.V., 2024)
The diagnosis of heart failure with preserved ejection fraction requires an integrative approach of clinical, biochemical and imaging evidence of left ventricular (LV) diastolic dysfunction (DD).